PEMANTAUAN RUMAH KACA DENGAN APLIKASI BLYNK CLOUD DI IKLIM SEMI-KERING - Bunga, Fredrik J. Haba; Dethan, Jemmy D S; Sabuna, Melani; Bullu, Novi I; Abineno, Jemseng C (Universitas Nusa Cendana, 2024)
Monitoring temperature and humidity during growth plants are very important Because impact significant on speed growth, productivity, and quality plant. Optimal temperature influences photosynthesis, transpiration, and development flower / fruit. Humidity tall help absorption of water and nutrients, reducing risk damage consequence change temperature extreme. Monitoring temperature and humidity also help detect and resolve problem plant. Study This aim For designing system IoT- based for monitor temperature and humidity plants at home glass. Study This test performance system as IoT tools for observation. Device design involve preparation equipment and manufacture code Arduino source (C++) for Arduino, which is connected through jumper cables to the DHT11 sensor and NodeMCU ESP8266. Blynk configuration allows Android devices with application the For display data, include temperature and humidity House glass. By Simultaneous, monitoring daily take notes change temperature moment apply devices at home glass hydroponics in Kupang City, East Nusa Tenggara Province. Research result show that system consists from device IoT hardware ( NodeMCU ESP8266 and Sensor DHT11) and components device software (Arduino IDE and Blynk), everything works with effective. Testing tool with a hygrometer and micrometre produce difference average temperature / humidity in the house glass of 1.33%, and humidity amounting to 2.17%. The error average temperature is 1.40%, with humidity of 2.35%.